Evaluation of Mchare and Matooke Bananas for Resistance to Fusarium oxysporum f. sp. cubense Race 1 - Ndayihanzamaso, P.; Mostert, D.; Matthews, M.C.; Mahuku, George S.; Jomanga, K.; Mpanda, H.J.; Mduma, H.; Brown, A.; Uwimana, Brigitte; Swennen, Rony L.; Tumuhimbise, Robooni; Viljoen, Altus (MDPI, 2020)
Fusarium wilt, caused by the soil-borne fungus Fusarium oxysporum f. sp. cubense (Foc) race 1, is a major disease of bananas in East Africa. Triploid East African Highland (Matooke) bananas are resistant to Foc race 1, but the response of diploid (Mchare and Muraru) bananas to the fungus is largely unknown. A breeding project was initiated in 2014 to increase crop yield and improve disease and pest resistance of diploid and triploid East African Highland bananas. In this study, eight Mchare cultivars were evaluated for resistance to Foc race 1 in the field in Arusha, Tanzania. In addition, the same eight Mchare cultivars, as well as eight Muraru cultivars, 27 Mchare hybrids, 60 Matooke hybrids and 19 NARITA hybrids were also screened in pot trials. The diploid Mchare and Muraru cultivars were susceptible to Foc race 1, whereas the responses of Mchare, NARITAs and Matooke hybrids ranged from susceptible to resistant. The Mchare and Matooke hybrids resistant to Foc race 1 can potentially replace susceptible cultivars in production areas severely affected by the fungus. Some newly bred Matooke hybrids became susceptible following conventional breeding, suggesting that new hybrids need to be screened for resistance to all Foc variants.